A robust computational technique for a system of singularly perturbed reaction-diffusion equations - Kumar, Vinod; Bawa, Rajesh K.; Lal, Arvind K. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a singularly perturbed system of reaction?diffusion Boundary Value Problems (BVPs) is examined. To solve such a type of problems, a Modified Initial Value Technique (MIVT) is proposed on an appropriate piecewise uniform Shishkin mesh. The MIVT is shown to be of second order convergent (up to a logarithmic factor). Numerical results are presented which are in agreement with the theoretical results.
Keywords: asymptotic expansion approximation; backward difference operator; trapezoidal method; piecewise uniform Shishkin mesh